"O meu é mais grande": rotinas lúdicas de comparação nas culturas da infância e apropriação de práticas de numeramento por crianças de 3 e 4 anos em uma escola municipal de educação infantil - Raquel Monteiro Pires de Lima (2020)
In this study, we analyze the ways in which a group of 3- and 4-years-old children, in a Belo Horizonte Municipal School of Early Childhood Education, appropriates numeracy practices. Such practices were caught in the interlocutions between children and theirs with the teacher. Our intention is show how children feature the process of appropriation of numeracy practices that were not intentionally provoked by the school didactic action, although they are practices forged by the school culture, conditioned by the space-time structure in which they are performed and by the materials available there, among others instruments and circumstances of the school context. The analysis was performed taking as reference the concept of numeracy practices, understood as sociocultural practices of production and use of knowledge that we identified associated with hegemonic mathematics and contributions from the Sociology of Childhood. Our analysis highlighted how numeracy practices integrate the grammar of childhood cultures and sought to understand how such practices are appropriated (made proper and used pragmatically) by children, seeking to identify their marks in the interlocutory games that are established in this group. We select numeracy events (which we identify as) in which children playing with construction toys, create and feature comparison games of different sizes. Children's performances in these games are understood as pragmatic, playful and interactive actions, and as such, they produce a system of meanings that, incorporating ideas, vocabulary, procedures, criteria, arguments and discourses of social practices (including numeracy practices) of the different groups in which children participate make up their peer culture.